The Influence of Fraud Triangle Framework on the Fraud Prevention and Detection Programs in PT. XX - Gabriela, Miranda Bethseba (Integrasi Sains Media, 2023)
Given the significant variability of fraud instances in businesses of all sizes, it is captivating that despite their complexity, the fraud triangle's three elements can be used to explain all of them. As a result, the researcher was compelled to examine the impact of this framework on fraud programs. This report aims to thoroughly analyze the fraud triangle's influence on fraud prevention and detection programs, particularly at PT. XX. This qualitative research data collection comprises two main target population sources, the internal auditor team and the company's management, through a semi-structured interview approach where data is later processed using the in vivo and pattern coding technique. It is found from the study that each dimension of the fraud triangle which are pressure, opportunity, and rationalization, has a direct causal link to a fraud program described in the company's fraud SOP. The analysis concluded that the internal auditor team used the fraud triangle framework to identify patterns in fraud justifications and then developed several preventive fraud programs that management and users will implement to reduce the amount of fraud occurring in PT. XX. Further findings included the mutually reinforcing roles undertaken by the two divisions under study in creating the SOP and carrying out the company's fraud programs, which the study contends have already been effectively executed.